(untitled) (American International Journal of Economics and Finance Research, 2019)
The aim of this study is to determine the impact of transactional and transformational leadership styles on employee performance in Nigeria Institute for Trypanosomiasis Research, Kaduna State. A structured questionnaire was used to sample respondents using simple random sampling technique. Multifactor Leadership Questionnaire (MLQ-5X) was used to measure leadership styles and employee performance was measured using salary, job experience and job satisfaction. A total of 230 questionnaires were distributed to the respondents. Structural equation model was used to analyze data using partial least squares method SmartPLS2. The result showed that transformational and transactional leadership styles has a significant and positive impact on employee performance. Therefore, it saw recommended that Nigeria Institute for Trypanosomiasis Research should practice transformational leadership styles to improve employee performance in the organization in Kaduna State.